Identities, Experience, and Change in Early Mexican Villages - Santasilia, Catharina E.; Hepp, Guy David; Diehl, Richard A. (University Press of Florida, 2022)
This work examines shifting social identities, lived experiences, and networks of interaction in Mexico during the Mesoamerican Formative period (2000 BCE-250 CE), an era that helped produce some of the world's most renowned complex civilisations. The chapters offer significant data, innovative methodologies, and novel perspectives on Mexican archaeology. Using diverse and non-traditional theoretical approaches, contributors discuss interregional relationships and the exchange of ideas in contexts ranging from the Gulf Coast Olmec region to the site of Tlatilco in Central Mexico to the often-overlooked cultures of the far western states. Their essays explore identity formation, cosmological perspectives, the first hints of social complexity, the underpinnings of Formative period economies, and the sensorial implications of sociocultural change.